Gastrointestinal manifestations of systemic mast cell activation disease - A practice-oriented guide to clinical picture, diagnostics and therapy Gastrointestinale Erscheinungsformen der systemischen Mastzellaktivierungserkrankung – Eine praxisorientierte Einführung in Klinik, Diagnostik und Therapie - Raithel, Martin; Homann, Jürgen; Rieker, Ralf; Molderings, Gerhard J. (Zeitschrift für Gastroenterologie, 2025)
Systemic mast cell activation disease (MCAD) is an epigenetic and genetic disease entity with a very pronounced clinical symptomatology in a variety of clinical manifestations in potentially every organ and tissue due to inappropriate release of mast cell mediators accompanied with the accumulation of both morphologically normal and mutated mast cells. Due to the prevalence of the disease of 17% in Germany, gastroenterologists and endoscopists are often unknowingly faced with MCAD in everyday clinical practice. In addition, gastroenterological examinations are an essential part of the diagnosis of MCAD. It is therefore essential for every physician working in gastroenterology to possess basic knowledge of this disease and, in particular, to be informed about its problems in the field of gastroenterology. This overview summarizes the current state of knowledge on the causes, diagnosis and treatment of the highly complex MCAD, focusing on the gastroenterological aspects.
CRIS-Team Scopus Importer:2025-02-28